The impact of life events on NSSI among left-behind college students: the mediating role of PLEs and the moderating role of social support - Hongcai Wang; Hongcai Wang; Yali Fu; Zihao Zeng; Lulu Lin; Qianyu Cheng; Juan Zhao; Yiqiu Hu; Yiqiu Hu; Yiqiu Hu (Frontiers in Psychology)
This study investigated the relationship between life events and non-suicidal self-injury (NSSI) among Chinese college students with left-behind experiences, focusing on the mediating role of Psychotic-like experiences (PLEs) and the moderating role of social support in this relationship. A total of 7,577 students were surveyed using the Adolescent Self-Rating Life Events Checklist (ASLEC), 8 positive symptom items from the Community Assessment of Psychic Experiences (CAPE), the Perceived Social Support Scale (PSSS), and the Deliberate Self-Harm Inventory (DSHI). After excluding invalid questionnaires, 5,754 were retained, of which 2,772 college students had left-behind experiences. The results show that (1) The prevalence of NSSI among college students with left-behind experiences was 11.51%, which was higher than that of college students without left-behind experiences (9.66%); (2) PLEs partially mediated the effect of life events on NSSI; (3) Social support moderated the first-stage path, second-stage path, and direct path of the mediation model by attenuating the effects of life events on PLEs, PLEs on NSSI, and the direct effects of life events on NSSI. So, we conclude that, among college students with left-behind experiences, PLEs mediate the effect of life events on NSSI, while social support moderates the mediation model by influencing the first-stage path from life events to PLEs, the second-stage path from PLEs to NSSI, and the direct path from life events to NSSI.